2015
DOI: 10.1080/19440049.2014.996789
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fast isocratic LC-MS/MS method for the high-throughput analysis of pyrrolizidine alkaloids in Australian honey

Abstract: Honey samples originating from Australia were purchased and analysed for targeted pyrrolizidine alkaloids (PAs) using a new and rapid isocratic LC-MS/MS method. This isocratic method was developed from, and is comparable with, a gradient elution method and resulted in no loss of sensitivity or reduction in chromatographic peak shape. Isocratic elution allows for significantly shorter run times (6 min), eliminates the requirement for column equilibration periods and, thus, has the advantage of facilitating a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Internationally it has been reported that such toxins can be found in honey due to transfer by bees of pollen/nectar from certain flowers, including Heliotropium, Crotolaria, Echium and Senecio species. Concern has been raised as to the extent of contamination in Australian honey [11,12] but their presence in Queensland honey has not previously been examined. Previously, investigations into the presence of PAs in Australian honey have concentrated on the introduced pest plant Echium plantagineum L. (Paterson's curse) as the major likely PA source [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally it has been reported that such toxins can be found in honey due to transfer by bees of pollen/nectar from certain flowers, including Heliotropium, Crotolaria, Echium and Senecio species. Concern has been raised as to the extent of contamination in Australian honey [11,12] but their presence in Queensland honey has not previously been examined. Previously, investigations into the presence of PAs in Australian honey have concentrated on the introduced pest plant Echium plantagineum L. (Paterson's curse) as the major likely PA source [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Concern has been raised as to the extent of contamination in Australian honey [11,12] but their presence in Queensland honey has not previously been examined. Previously, investigations into the presence of PAs in Australian honey have concentrated on the introduced pest plant Echium plantagineum L. (Paterson's curse) as the major likely PA source [11][12][13]. However, rigorous eradication and biological control programs in recent decades have decreased the prevalence of this weed in Australia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Around 40% of Europe's consumption needs are met through honey imports (CBI 2017). As it was revealed, the honey of Central and South America or Australia can contain high rates of PA positive samples with high individual PA levels (EFSA 2011;Dübecke et al 2011;Griffin et al 2015a;Valese et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Senecio jacobaea , tansy ragwort) in the U.K. and from Echium plantagineum growing in Australia, respectively [ 16 , 17 ]. Since then, several studies worldwide (summarized in chronological order in Table S1 ) focused on developing methods and identifying PA/PANO in honey from known plant sources and geographical origins (examination of raw/bulk or regionally produced honey) [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and in honey from retail [ 19 , 20 , 21 , 24 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Raw and regionally produced honeys showed higher PA/PANO levels than blended retail honeys, while the latter usually showed higher rates of contamination.…”
Section: Introductionmentioning
confidence: 99%